The Bcl-2-associated athanogene gene family in tobacco (Nicotiana tabacum) and the function of NtBAG5 in leaf senescence - Gu, Linxin; Hou, Bing; Chen, Xiao; Wang, Yu; Chang, Pingan; He, Xiaohong; Gong, Daping; Sun, Quan (Frontiers in Plant Science, 2023)
Leaf senescence in tobacco is closely related to leaf maturation and secondary metabolites. Bcl-2-associated athanogene (BAG) family members are highly conserved proteins and play key roles in senescence, growth and development, and resistance to biotic and abiotic stresses. Herein, the BAG family of tobacco was identified and characterized. In total, 19 tobacco BAG protein candidate genes were identified and divided into two classes, class I comprising NtBAG1a–e, NtBAG3a–b, and NtBAG4a–c and class II including NtBAG5a–e, NtBAG6a–b, and NtBAG7. Genes in the same subfamily or branch of the phylogenetic tree exhibited similarities in gene structure and the cis-element on promoters. RNA-seq and real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) revealed that the expression of NtBAG5c–f and NtBAG6a–b was upregulated in senescent leaves, implying that they play a role in regulating leaf senescence. NtBAG5c was localized in the nucleus and cell wall as a homology of leaf senescence related gene AtBAG5. Further, the interaction of NtBAG5c with heat-shock protein 70 (HSP70) and sHSP20 was demonstrated using yeast two-hybrid experiment. Virus-induced gene silencing indicated that NtBAG5c reduced the lignin content and increased superoxide dismutase (SOD) activity and hydrogen peroxide (H2O2) accumulation. In NtBAG5c-silenced plants, the expression of multiple senescence-related genes cysteine proteinase (NtCP1), SENESCENCE 4 (SEN4) and SENESCENCE-ASSOCIATED GENE 12 (SAG12) was downregulated. In conclusion, tobacco BAG protein candidate genes were identified and characterized for the first time.